Prawne podstawy wykonywania zawodu psychologa = The Legal basis of profession of psychologist - Agata Klimczyk (Kazimierz Wielki University, 2015)
Klimczyk Agata. Prawne podstawy wykonywania zawodu psychologa = The Legal basis of profession of psychologist. Journal of Education, Health and Sport. 2015;5(8):280-284. ISSN 2391-8306. DOI 10.5281/zenodo.28671 http://dx.doi.org/10.5281/zenodo.28671 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A280-284 https://pbn.nauka.gov.pl/works/610938 POL-index https://pbn.nauka.gov.pl/polindex/browse/article/article-e195f758-2eab-4c9f-aa41-41fea649d620 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 20.07.2015. Accepted: 18.08.2015.   Prawne podstawy wykonywania zawodu psychologa The Legal basis of profession of psychologist   Agata Klimczyk   Nicolaus Copernicus University in Toruń   Streszczenie          Celem pracy jest przedstawienie prawnych uregulowań związanych z zawodem psychologa.  W pracy posłużono się materiałami źródłowymi z zakresu omawianej tematyki i odniesieniem do Ustawy o zawodzie psychologa i samorządzie zawodowym psychologów. Autor skupia się  na wymaganiach stawianych psychologom. Możliwość poniesienia odpowiedzialności dyscyplinarnej dodatkowo wpływa na rzetelne wykonywanie zawodu. Równowaga psychiczna stanowi podstawę ładu społecznego, stąd wzrasta ranga tego zawodu.   Słowa kluczowe: prawo, zawód, psychologia, psycholog.   Abstract   The aim of this work is to show legal basis related to profession of psychologist. In the work was used special literature and legal regulations. The author focuses on requirements for psychologists. The author notes that psychologists are disciplinary responsible for their work, what can have influence on quality of their job, and equilibrium is a base of social peace. Therefore significance of this profession grows.   Key worlds: profession law, psychology, psychologist.